Educational strategies in data journalism: A comparative study of six European countries. (January 2016) - Splendore, Sergio; Di Salvo, Philip; Eberwein, Tobias; Groenhart, Harmen; Kus, Michal; Porlezza, Colin
The article explores training programs in higher education with regard to data journalism from a multi-national perspective. By carrying out a comparative analysis in six European countries (Germany, Switzerland, the Netherlands, Italy, Poland, and the United Kingdom), it covers different models of media systems and journalistic cultures envisaged by Hallin and Mancini. Based on a desk review and in-depth interviews with instructors of data journalism in each country, the article identifies different approaches to the way data journalism is taught. In Europe, such programs are offered by four types of organizations: academic, vocational, professional, and civic. The role played by those organizations can be explained as a result of the peculiarities of national media systems. But there are also commonalities, for example, non-academic institutions (such as the European Journalism Center or the Center for Investigative Journalism) and major international news outlets (such as The Guardian and The New York Times ) seem to take over a leading role in all of the analyzed countries. Generally speaking, data journalism education appears to be a very young discipline that frequently neglects fundamental journalistic topics such as ethical issues, transparency, accountability, and responsiveness although they are crucial in a journalistic field as sophisticated tools to reveal hidden aspects of reality.